Short selling and trade credit: New evidence - Xin Xiang; Xu He (Borsa İstanbul Review, 2024)
This study investigates the effect of short sales on firms' use of trade credit. Using a sample of 3262 Chinese listed firms from 2007 to 2019, the analysis results show that both the deregulation and the magnitude of short sales negatively affect trade credit. The transmission mechanism indicates that firms' access to formal financing decreases after short sales deregulation, which mitigates firms' ability to redistribute formal financing through trade credit. Moreover, the results suggest that shortable firms tend to adopt a moderate trade credit policy and adjust their trade credit to the target level at a lower rate than non-shortable firms. This study reveals the features of the short sales–trade credit relationship in an emerging market.
Keywords: G18; G32; G38; G14; 330; Short sales; Trade credit; Financing effect; Deterrent effect